Marker-based pedigree reconstruction reveals limited diversity within commercial Eucalyptus benthamii breeding populations in Brazil - Ferreira, Filipe Manoel [UNESP]; Grattapaglia, Dario; Bush, David; Andrejow, Gisela Maria Pedrassani; Estopa, Regiane Abjaud; Tambarussi, Evandro Vagner [UNESP] (Springer Nature, 2024)
Despite extensive introductions of Eucalyptus germplasm to Brazil in the last 50 years, relatively little is known about the genetic diversity within current breeding programs, particularly for non-mainstream species. A prime example is Eucalyptus benthamii, a subtropical species with a restricted natural range, endangered due to anthropogenic population fragmentation. We used microsatellite markers to reconstruct the pedigrees and estimate diversity within the two most representative pools of E. benthamii germplasm managed in separate, commercial Brazilian breeding populations. The analysis, together with evidence from Australian Tree Seed Centre (ATSC), historical germplasm export data confirmed that the genetic diversity within the two populations is modest. In the two breeding populations, the estimated status number was in the range of 8.5–22.0 per population considering marker-based co-ancestry. Extensive close relatedness and family structure were identified within and across the two populations, confirming that they share a high proportion of founder ancestors. This is likely a result of the narrow genetic base of the initial introductions and subsequent directional selection and breeding. With the increasing importance of E. benthamii in Brazilian plantation forestry, and as further breeding will likely reduce the status number, our study highlights the need for infusions to augment the existing genetic diversity. Complementary to sourcing infusions, implementing breeding strategies that take advantage of the marker-based information reported in this study to carefully manage the pedigree should help to minimise inbreeding. Exchanging unrelated individuals between the two Brazilian breeding populations would also be advantageous.
Keywords: Genetic diversity; Microsatellites; Molecular breeding